2011
DOI: 10.1007/s13157-011-0199-y
|View full text |Cite
|
Sign up to set email alerts
|

Road Salt Stress Induces Novel Food Web Structure and Interactions

Abstract: Freshwater salinization is an emerging global concern, and in northern latitudes can be largely attributed to road deicer applications during winter and spring. To investigate the effects of road salt contamination on pond food webs, we manipulated trophic structure and salt in experimental pond communities. In May 2008, we inoculated forty 600-L pond mesocosms with algae and zooplankton. Using a full-factorial design, we manipulated road salt presence (645 mg L −1 Cl − ) and tadpoles (Hyla versicolor) in a fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
86
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(102 citation statements)
references
References 44 publications
(64 reference statements)
11
86
5
Order By: Relevance
“…However, gray treefrog larvae that persist during these early developmental stages do have high survival rates as they develop through metamorphosis in high salt concentrations [31]. Furthermore, these individuals reared under elevated chloride conditions experience faster time to and larger size at metamorphosis [25], [31]. We obtained gray treefrog embryos for these previous studies from PWRC which is a rather pristine and protected environment.…”
Section: Discussion/conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, gray treefrog larvae that persist during these early developmental stages do have high survival rates as they develop through metamorphosis in high salt concentrations [31]. Furthermore, these individuals reared under elevated chloride conditions experience faster time to and larger size at metamorphosis [25], [31]. We obtained gray treefrog embryos for these previous studies from PWRC which is a rather pristine and protected environment.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Although we cannot rule out large changes in dissolved oxygen or pH over the course of the study, our previous research in these artificial pond systems suggested there would be no dramatic shifts in either of these parameters and no systematic shifts with our study treatments [25]. Given the high nitrogen content of waste released by developing tadpoles [36], we also collected water samples on day 45 to obtain nitrate estimates.…”
Section: Methodsmentioning
confidence: 99%
“…Salinity is known as a driving force governing the composition of aquatic ecological communities (Gunter 1956), and recent work has suggested that salinity can affect the interactions of amphibians with other community members (e.g., food-web dynamics) both directly and indirectly (Petranka and Doyle 2010;Chambers 2011;Van Meter et al 2011;Petranka and Francis 2013;Moreira et al 2015;Van Meter and Swan 2014). Adaptation to salinity could certainly lead to novel predation opportunities for amphibians in these environments, as has been shown in some South American anurans eating marine invertebrates, for example (Sazima 1971;Brasileiro et al 2010;Ferreira and Tonini 2010).…”
Section: Origins Of Salt Tolerancementioning
confidence: 99%
“…Now, through this new work, we have estimated that 76 % of surface water area and at least 45 % of stream length (dependent on buffer width) in the Park may be receiving road runoff pollutants such as salt. Salt is one of the most widely studied road runoff pollutants, and the effects of salinization on freshwater ecosystems are well documented; for example, studies have reported reduced aeration and water circulation at depth (Fay and Shi 2012), decreased spotted salamander (Ambystoma maculatum) and wood frog (Rana sylvatica) survival (Karraker et al 2008), shifts in community structure (Collins and Russel 2009), reduced copepod density and changes in algal resources (Meter et al 2011), and decreased productivity at all trophic levels in model freshwater communities (Dalinsky et al 2014). A significant amount of road salt also enters groundwater where it can accumulate over years and exceed thresholds for potable water and aquatic organisms (Perera et al 2012).…”
Section: Impacted Lands and Watersmentioning
confidence: 99%